2022
DOI: 10.3389/ffgc.2022.1046606
|View full text |Cite
|
Sign up to set email alerts
|

Defensive patterns of chestnut genotypes (Castanea spp.) against the gall wasp, Dryocosmus kuriphilus

Abstract: Plants draw from various genetically controlled defenses to protect against herbivores and pathogens. The efficacy of alternative defenses can vary with the biology and phylogeny of the enemy. Dryocosmus kuriphilus, an invasive gall maker native to China, has become one of the main pests of chestnut trees around the world. We studied genetic variation in resistance and susceptibility to D. kuriphilus within a replicated blocked planting of 12 chestnut genotypes established in Galicia, Spain in 2004. We found v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…Genetic analysis (identification of molecular markers) of two trees of each class, carried out by Functional Genomics and Sequencing Platform (RIAIDT) of the University of Santiago de Compostela, confirmed that the trees belong to different hybrid clones: "324" and "502" in "Esperante" and "324" and "HS" in "O Corgo." No galls were found in trees of clone "324, " which is known to be resistant to the gall wasp (Míguez-Soto et al, 2018;Castedo-Dorado et al, 2021;Lombardero et al, 2022), whereas galls were present in trees of both "502" and "HS" clones. In the remaining 14 plots, we found that the level of gall wasp attack varied across the trees.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis (identification of molecular markers) of two trees of each class, carried out by Functional Genomics and Sequencing Platform (RIAIDT) of the University of Santiago de Compostela, confirmed that the trees belong to different hybrid clones: "324" and "502" in "Esperante" and "324" and "HS" in "O Corgo." No galls were found in trees of clone "324, " which is known to be resistant to the gall wasp (Míguez-Soto et al, 2018;Castedo-Dorado et al, 2021;Lombardero et al, 2022), whereas galls were present in trees of both "502" and "HS" clones. In the remaining 14 plots, we found that the level of gall wasp attack varied across the trees.…”
Section: Study Areamentioning
confidence: 99%
“…This pest, commonly known as the Asian chestnut gall wasp, is native to China and can affect species of the genus Castanea and hybrid clones. Nevertheless, a wide range of variability among clones regarding the level of infestation by D. kuriphilus has been reported, suggesting a genotype-dependent variation in susceptibility (Sartor et al, 2015;Míguez-Soto et al, 2018;Castedo-Dorado et al, 2021;Lombardero et al, 2022). The same applies to the European populations of C. sativa, suggesting that the differences are due to specific features of individual trees within the populations (Bombi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Barr. together with the plague of chestnut gall wasp Dryocosmus kuriphilus Yasumatsu have caused great damage to these agroforestry systems [13,22]. Another threat is that of forest fires, which may increase in frequency, size, and intensity due to the increasing rates of biomass accumulation associated with land abandonment and to climate warming [23].…”
Section: Introductionmentioning
confidence: 99%
“…Variability in the intensity of ACGW attacks, up to resistance, was observed in the different species of chestnut [11][12][13]. Dini et al [14] and Lombardero et al [13] highlighted the defensive patterns of chestnut against ACGW and identified the hypersensitive reaction (HR) as a mechanism of resistance in resistant hybrid genotypes.…”
Section: Introductionmentioning
confidence: 99%